Share pledging and financial constraints in China. (3rd December 2020) - Cheng, Zijian; Liu, Zhangxin (Frank); Sun, Yupu
Abstract: We investigate the relationship between the intensity of share pledging activities and the level of financial constraint in publicly listed firms in China. We show that the high financial constraint level may motivate insiders to use share pledging as an alternative funding source and an expropriation mechanism. Although overall share collateralisation can cause a subsequently more constrained financing condition, we find evidence that share pledging made by the controlling shareholder is likely to mitigate financial constraints in the following year. Our findings are robust to alternative measures and an instrumental variable for dealing with endogeneity problems.